Xanthine Derivative KMUP-1 Attenuates Experimental Periodontitis by Reducing Osteoclast Differentiation and Inflammation - Kuo, Cheng-Hsiang; Zhang, Ban-Hua; Huang, Shang-En; Hsu, Jong-Hau; Wang, Yan-Hsiung; Nguyen, Thi Tuyet Ngan; Lai, Chao-Han; Yeh, Jwu-Lai (Frontiers in Pharmacology, 2022)
Periodontitis is an inflammatory disease of gum that may predispose to serious systemic complications such as diabetes and cardiovascular diseases. Activation of macrophages and osteoclasts around periodontal tissue can accelerate gum inflammation. In addition, alteration of cyclic nucleotide levels is associated with the severity of periodontitis. Our previous study has shown that KMUP-1, a xanthine derivative exhibiting phosphodiesterase inhibition and soluble guanylyl cyclase activation, can inhibit lipopolysaccharide (LPS)-induced inflammation and receptor activator of nuclear factor kappa-Β ligand (RANKL)-induced osteoclastogenesis. This study was aimed to investigate whether KMUP-1 could attenuate periodontitis both in vitro and in vivo. In vitro, the protective effect of KMUP-1 on inflammation and osteoclastogenesis was investigated in RANKL-primed RAW264.7 cells treated by Porphyromonas gingivalis LPS (PgLPS). The results showed that KMUP-1 attenuated PgLPS-induced osteoclast differentiation as demonstrated by decreased TRAP-positive multinuclear cells and TRAP activity. This reduction of osteoclast differentiation by KMUP-1 was reversed by KT5823, a protein kinase G inhibitor. Similarly, pro-inflammatory cytokine levels induced by PgLPS were inhibited by KMUP-1 in a dose-dependent manner whereas reversed by KT5823. Mechanistically, suppression of MAPKs, PI3K/Akt, and NF-κB signaling pathways and decrease of c-Fos and NFATc1 expression in osteoclast precursors by KMUP-1 may mediate its protective effect. In vivo, two models of periodontitis in rats were induced by gingival injections of PgLPS and ligature placement around molar teeth, respectively. Our results showed that KMUP-1 inhibited alveolar bone loss in both rat models, and this effect mediated at least partly by reduced osteoclastogenesis. In conclusion, our study demonstrated the therapeutic potential of KMUP-1 on periodontitis through suppression of inflammation and osteoclast differentiation.